Teleological renunciation of the moral in the absolute paradox motif: A dialectical analysis of kierkegaardian infinite resignation in existential theism and bahala na - Tabuena, Larnie Sam Aldea (Animo Repository, 1999)
The individual's passionate quest for an authentic mode of being expresses the universal phenomenon of a recurring pathological obsession with contingency. The synthesis of the finite and the infinite in human self presupposes its possibility of becoming, toward the absolute telos. Ultimate concern is an existential pathos in response to the threat of non-being. Self-alienation to the Ground of its being brought disintegration, despair, and incompleteness in human experience. The concept of transformational reciprocity of the finite self with the absolute Self is an ontological necessity to establish certain qualifications to justify the movement of infinite resignation as an act of willful participation to the Ground of its being. Faith then, as an integrative principle of existence, is a soul's inner wisdom, spiritual sight, religious apperception in realizing one's eternal validity as well as an act of total faculties upon entering a relation with the Unknown. By embracing the Absolute paradox, the Absurd, an individual stands higher than the universal by the virtue of his absolute relation to the absolute. The idea of teleological renunciation of the moral came into being as an existential parlance. The philosophical methodology employed a dialectical analysis through critical synthetic-thought reformulation presupposing qualitative polarities between the theistic existentialist concept of infinite resignation and the Filipino ethico-religious world-life-view reflected in bahala na trait. In the review of selected related literature, the relatively few available written scholarly materials are classified under romantic fideism, theistic existentialism, and intuitionism and mysticism. The underlying theoretical presupposition that has been the groundwork for the development of this study is the notion of an existential ontology of the dialectic structure of faith.The section on the movement of infinite resignation investigates the psychological dissonance of the self and its possibility to achieve eternal validity by means of renouncing all finite relativities. The confrontation of the finite individual and the Eternal Thou brings ontological clarification as well as metamorphosis of being. Man's facticity through his freedom points to the truth that his absolute relation to the Absolute will enable him to transcend the mournful curtailments of the soul.The section on bahala na investigates the indigenous theocentric consciousness and religious propensity of a Filipino whenever his personal deficiency makes him incapable to confront squarely life's uncertainties. Optimistic fatalism evolves a trajectory resulting from a supernaturalistic theology/belief in divine omnipotence and providence. The utterance itself is also an attribute of genuine faith, an attitude of risk-taking entrepreneurship, and resolute determination to rise above an adverse states into the achievement of existential equilibrium.The section on logocentered discourse on rationality and praxis is a dialectical analysis of infinite resignation and bahala na which led to a critical reformulation of existential ontology toward authentic mode of being and thinking. The logos as a rational principle is embedded in human inner constitution